Carbonate Facies and Depositional Environment of Pre-Parigi Carbonate in Ardjuna Sub-basin: Application of Core-facies Coding and Electro-facies - Muhammad Virgiawan Agustin; Salahuddin Husein; Jarot Setyowiyoto; Rahmat Rahmat (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2023)
The Pre-Parigi Formation is one of the formations in the West Java Basin North as a potential reservoir. However, the carbonate rocks of the Pre-Parigi Formation are considered to have high heterogeneity due to rock and depositional processes its diagenesis, so an appropriate approach is needed to understand its reservoir distribution. Therefore, in this study, interpretation of the facies distribution of the Pre-Parigi Formation was carried out using the integration of core data and well logs. On the core data, facies coding and clustering is performed to interpret the facies association. Then, the identified facies associations are integrated with the characters so that facies interpretation can be carried out for all intervals and all wells. The end result is an interpretation of the distribution of the facies of Pre-Parigi Carbonate. Based on the analysis results, the Pre-Parigi Carbonate in the study area is composed of five facies associations, such as deep shelf (FA 1), fore-slope (FA 2), near-reef lagoon (FA 3), lagoon (FA 4), and restricted circulation shelf – tidal flat (FA 5). FA 1 is characterized by a very high value, slightly serrated gamma-ray character. FA 2 is characterized by a high gamma-ray, serrated, intercalated with a fining-upward low gamma-ray layer, FA 3 is characterized by a low value and blocky gamma-ray, FA 4 is also characterized by a gamma-ray with a fairly low value, but has a pattern that tends to be serrated, and then FA 5 is characterized by a serrated gamma-ray character with a slightly higher value than FA 4. Based on the integration of all interpretations, the Pre-Parigi Carbonate in the study area can be divided into three depositional sequences (DS), where DS-1 develops in all area as a reef-initiation, DS-2 developed in the MVA-1 and MVA-3 wells, and did not develop in the MVA-6 well (had a give-up phase), and then DS-3 only developed in the MVA-3 well. In general, facies interpretation using the core-facies coding and electro-facies characterizing methods tends to be effective and provides more confidence interpretation. Keywords: Pre-Parigi Carbonate, Carbonate facies, Core-facies coding, Arjuna Sub-basin